A comparison between rebound and Goldmann’s tonometers in screening of patients for glaucoma - Agrawal, A; Pratap, VP; Pal, VK; Suman, S (Nepalese Journal of Ophthalmology, 2012)
DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5880 NEPJOPH 2012; 4(1): 201-202